Ion Flux Dependent and Independent Functions of Ion Channels in the Vertebrate Heart: Lessons Learned from Zebrafish - Mirjam Keßler; Steffen Just; Wolfgang Rottbauer (Stem Cells International)
Ion channels orchestrate directed flux of ions through membranes and are essential for a wide range of physiological processes including depolarization and repolarization of biomechanical activity of cells. Besides their electrophysiological functions in the heart, recent findings have demonstrated that ion channels also feature ion flux independent functions during heart development and morphogenesis. The zebrafish is a well-established animal model to decipher the genetics of cardiovascular development and disease of vertebrates. In large scale forward genetics screens, hundreds of mutant lines have been isolated with defects in cardiovascular structure and function. Detailed phenotyping of these lines and identification of the causative genetic defects revealed new insights into ion flux dependent and independent functions of various cardiac ion channels.